2019
DOI: 10.1002/adfm.201908411
|View full text |Cite
|
Sign up to set email alerts
|

All‐Fiber Structured Electronic Skin with High Elasticity and Breathability

Abstract: With the rapid advancement in artificial intelligence, wearable electronic skins have attracted substantial attention. However, the fabrication of such devices with high elasticity and breathability is still a challenge and highly desired. Here, a route to develop an all-fiber structured electronic skin with a scalable electrospinning fabrication technique is reported. The fabricated electronic skin is demonstrated to exhibit high pressure sensing with a sensitivity of 0.18 V kPa −1 in the detection range of 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
161
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(176 citation statements)
references
References 42 publications
1
161
0
Order By: Relevance
“…[242] To overcome this, limited attempts have been made to develop breathable wearable devices utilizing 3D microarchitectures, structured fiber films, and porous polymers. [154,190,243] A recent study has shown significant suppression of the skin inflammation by designing nanomesh, ultrathin, and gas-permeable wearable devices. [244] Therefore, the research focus should move toward the development of wearable strain sensors using more biocompatible and clinically acceptable materials.…”
Section: Limitations and Challengesmentioning
confidence: 99%
“…[242] To overcome this, limited attempts have been made to develop breathable wearable devices utilizing 3D microarchitectures, structured fiber films, and porous polymers. [154,190,243] A recent study has shown significant suppression of the skin inflammation by designing nanomesh, ultrathin, and gas-permeable wearable devices. [244] Therefore, the research focus should move toward the development of wearable strain sensors using more biocompatible and clinically acceptable materials.…”
Section: Limitations and Challengesmentioning
confidence: 99%
“…The schematic shown in Figure 6 illustrates the use of yarns for developing electronic fabrics. The cross-over points between the elastic composite yarns serve as capacitive Using similar approach, textiles for wearable electronic skin applications can be developed by incorporating pressure-sensitive materials into the fabric [33][34][35]. For such applications, functional polymers such as piezoelectric or conductive polymers are typically used and integrated into the fabrics [36][37][38].…”
Section: Composite Fibers and Multilayer Nanofiber Membranementioning
confidence: 99%
“…Typically, such fabrications take place in the form of triboelectric modifications in yarn or fabric form. For instance, the fiber/yarn-based TENG fabrication methods include laboratory-scale electrospinning ( Li et al., 2020 ), wrapping or coiling with a motor ( Lou et al., 2020 ; Ye et al., 2020a ), twisting techniques ( Zhou et al., 2014a , 2014b ), etc. These yarns and fibers are typically embedded or converted into fabrics using sewing ( He et al., 2019 ; Lai et al., 2017 ), hand weaving ( Liu et al., 2019a , 2019b ; Zhang et al., 2016 ), shuttle weaving ( Chen et al., 2016 ), hand knitting ( Dong et al., 2017b ), pilot-scale nonwoven techniques ( Peng et al., 2019 ), and embroidery ( Sala de Medeiros et al., 2019 ) methods.…”
Section: Textile-based Tengsmentioning
confidence: 99%